Clustering properties of merger waves: Space, time or industry? - Florian Szücs (Deutsches Institut für Wirtschaftsforschung (DIW), 2013)
We study the degree of agglomeration of acquisition activity within clusters of temporal, geographic and industrial proximity based on almost 600,000 individual transactions. The findings indicate that significant clustering occurs in time and across industries, while the results on geographic clustering are mixed. This supports the view that merger waves are mostly driven by neoclassical motives.
Keywords: L2; G3; 330; merger wave; clustering; acquisitions; neoclassical; behavioral